"Przestrzeń dla rzeki" na przykładzie rozwiązań projektowych Wężyska - Chlebowo w województwie lubuskim = Room for the river on example of project solution Wężysko - Chlebowo in lubuskie province - Tonder, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article has attempted to display the two different conceptions concerning the aim of flood protection of the Odra valley which is situated between the Bóbr outlet and the Nysa Łużycka outlet. The first idea suggests building a new section of the flood bank and moving it further from the river whereas the second idea proposes a modernization of the existing flood bank, without any change to its localion.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)